The Peptidoglycan-associated lipoprotein Pal contributes to the virulence of Burkholderia mallei and provides protection against lethal aerosol challenge. Issue 1 (31st December 2020) - Dyke, Jeremy S.; Huertas-Diaz, Maria Cristina; Michel, Frank; Holladay, Nathan E.; Hogan, Robert J.; He, Biao; Lafontaine, Eric R.
ABSTRACT: Burkholderia mallei is a highly pathogenic bacterium that causes the fatal zoonosis glanders. The organism specifies multiple membrane proteins, which represent prime targets for the development of countermeasures given their location at the host-pathogen interface. We investigated one of these proteins, Pal, and discovered that it is involved in the ability of B. mallei to resist complement-mediated killing and replicate inside host cells in vitro, is expressed in vivo and induces antibodies during the course of infection, and contributes to virulence in a mouse model of aerosol infection. A mutant in the pal gene of the B. mallei wild-type strain ATCC 23344 was found to be especially attenuated, as BALB/c mice challenged with the equivalent of 5, 350 LD50 completely cleared infection. Based on these findings, we tested the hypothesis that a vaccine containing the Pal protein elicits protective immunity against aerosol challenge. To achieve this, the pal gene was cloned in the vaccine vector Parainfluenza Virus 5 (PIV5) and mice immunized with the virus were infected with a lethal dose of B. mallei . These experiments revealed that a single dose of PIV5 expressing Pal provided 80% survival over a period of 40 days post-challenge. In contrast, only 10% of mice vaccinated with a PIV5 control virus construct survived infection. Taken together, our data establish that the Peptidoglycan-associated lipoprotein Pal is a critical virulence determinant of B. mallei and effective target for developing a glanders vaccine.